New Evidence Supporting the Role of FBN1 in the Development of Adolescent Idiopathic Scoliosis. Issue 4 (15th February 2019) - Sheng, Fei; Xia, Chao; Xu, Leilei; Qin, Xiaodong; Tang, Nelson Leung-Sang; Qiu, Yong; Cheng, Jack Chun-Yiu; Zhu, Zezhang
Abstract : Study Design: A genetic association study. Objective: To determine whether common variants of fibrillin-1 ( FBN1 ) and fibrillin-2 ( FBN2 ) are associated with adolescent idiopathic scoliosis (AIS), and to further investigate to further investigate the functional role of FBN1 in the onset and progression of AIS. Summary of Background Data: Previous studies have identified several rare variants in FBN1 and FBN2 that were associated with AIS. There is, however, a lack of knowledge concerning the association between common variants of FBN1 and FBN2 and AIS. Methods: Common variants covering FBN1 and FBN2 were genotyped in 952 patients with AIS and 1499 controls. Paraspinal muscles were collected from 66 patients with AIS and 18 patients with lumbar disc herniation (LDH) during surgical interventions. The differences of genotype and allele distributions between patients and controls were calculated using Chi-square test. The Student t test was used to compare the expression of FBN1 and FBN2 between patients with AIS and LDH. One-way analysis of variance test was used to compare the gene expression among different genotypes of the significantly associated variant. The Pearson correlation analysis was used to determine the relationship between FBN1 expression and the curve severity. Results: The common variant rs12916536 of FBN1 was significantly associated with AIS. Patients were found to have significantly lower frequency of allele A than the controls (0.397 vs. 0.450, P = 1.10 × 10 −4 ) with an odds ratio of 0.81. Moreover, patients with AIS were found to have significantly lower FBN1 expression than patients with LDH (0.00033 ± 0.00015 vs. 0.00054 ± 0.00031, P = 1.70 × 10 −4 ). The expression level of FBN1 was remarkably correlated with the curve severity ( r = −0.352, P = 0.02). There was no significant difference of FBN1 expression among different genotypes of rs12916536. Conclusion: Common variant of FBN1 is significantly associated with the susceptibility of AIS. Moreover, the decreased expression of FBN1 is significantly correlated with the curve severity of AIS. The functional role of FBN in AIS is worthy of further investigation. Level of Evidence: 3 Abstract : Common variants covering fibrillin-1 ( FBN1 ) and fibrillin-2 ( FBN2 ) were genotyped in 952 patients with adolescent idiopathic scoliosis (AIS) and 1499 controls. Rs12916536 of FBN1 is significantly associated with AIS. Moreover, the decreased expression of FBN1 is significantly correlated with the curve severity of AIS. The functional role of FBN in AIS is worthy of further investigation.